2017
DOI: 10.5387/fms.2017-05
|View full text |Cite
|
Sign up to set email alerts
|

Apparent diffusion coefficient on magnetic resonance imaging (MRI) in bladder cancer: relations with recurrence/progression risk

Abstract: AIMS :To evaluate the relationship between the apparent diffusion coefficient (ADC) value for bladder cancer and the recurrence/progression risk of post -transurethral resection (TUR). METHODS : Forty -one patients with initial and non -muscle -invasive bladder cancer underwent MRI from 2009 to 2012. Two radiologists measured ADC values. A pathologist calculated the recurrence/progression scores, and risk was classified based on the scores. Pearson's correlation was used to analyze the correlations of ADC valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The VI‐RADS score might become a tool for prediction of both tumor aggressiveness and response to therapy, as well as a clinical predictor for perioperative outcomes. Several studies have demonstrated how MRI functional sequences are reliable in determining and predicting tumor aggressiveness 46,87–91 . Notably, ADC value quantification has been proposed as a potential biomarker by Kobayashi et al, showing that an ADC cutoff value of 0.86 × 10 –3 mm 2 /s (sensitivity of 88%, a specificity of 85%, and an accuracy of 87%) could be used to identify clinically aggressive phenotypes differentiating high grade tumors from less aggressive phenotypes 92 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The VI‐RADS score might become a tool for prediction of both tumor aggressiveness and response to therapy, as well as a clinical predictor for perioperative outcomes. Several studies have demonstrated how MRI functional sequences are reliable in determining and predicting tumor aggressiveness 46,87–91 . Notably, ADC value quantification has been proposed as a potential biomarker by Kobayashi et al, showing that an ADC cutoff value of 0.86 × 10 –3 mm 2 /s (sensitivity of 88%, a specificity of 85%, and an accuracy of 87%) could be used to identify clinically aggressive phenotypes differentiating high grade tumors from less aggressive phenotypes 92 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated how MRI functional sequences are reliable in determining and predicting tumor aggressiveness. 46,[87][88][89][90][91] Notably, ADC value quantification has been proposed as a potential biomarker by Kobayashi et al, showing that an ADC cutoff value of 0.86 × 10 -3 mm 2 /s (sensitivity of 88%, a specificity of 85%, and an accuracy of 87%) could be used to identify clinically aggressive phenotypes differentiating high grade tumors from less aggressive phenotypes. 92 A few years before Takeuchi et al proposed the ADC value as a predictor of BCa grading, there were significant differences between the values of G1 and G3 and between G2 and G3.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The combination of ADC and wash-out rate determined the BCa aggressiveness with 96.7% sensitivity, 94.9% specificity, and 95.7% accuracy [43]. Also, ADC was useful for determining the recurrence and progression risk of BCa [19, 40, 4446]. DWI-MRI however, helps distinguish benign and malignant bladder lesions, for staging, and for the assessment of efficacy of chemo-radiotherapy treatment [36].…”
Section: Introductionmentioning
confidence: 99%